2017
DOI: 10.1016/j.fuel.2017.07.018
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics and pore structure of sorbents during the simultaneous calcination/sulfation of limestone in CFB

Abstract: The interaction of calcination and sulfation in the simultaneous calcination/sulfation of limestone sorbent under circulating fluidized bed boiler conditions was studied. A specially designed constant-temperature reactor which can stop the reaction at a given time was employed. When limestone entered the furnace of mixed gases of CO2, O2, SO2, etc., its weight went down first, then up, so there was a minimum weight point. The whole reaction period could be divided into two stages by this minimum weight point, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
(50 reference statements)
2
12
0
Order By: Relevance
“…One more phenomenon to be noted in Figure b is that the samples under all four conditions were calcined completely at 300 s. This is different from the findings on Massicci limestone in the work of Wang et al, where they found that the samples which experienced 90 min of reaction still contained 3%–5% mass fraction of undecomposed CaCO 3 . The reason may be that the sulfation reactivity of the limestone used in the present work is lower than for Massicci limestone, as has been pointed out elsewhere …”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…One more phenomenon to be noted in Figure b is that the samples under all four conditions were calcined completely at 300 s. This is different from the findings on Massicci limestone in the work of Wang et al, where they found that the samples which experienced 90 min of reaction still contained 3%–5% mass fraction of undecomposed CaCO 3 . The reason may be that the sulfation reactivity of the limestone used in the present work is lower than for Massicci limestone, as has been pointed out elsewhere …”
Section: Resultsmentioning
confidence: 70%
“…For a spherical particle, η can be calculated by: η=3φ[]coth()φ1φ φ=Rkv/De where R is the radius of the particle, m; k v is the reaction rate constant per unit volume; and D e is the diffusion coefficient of CO 2 in pores of CaO layer. The procedure to calculate k v and D e can be found elsewhere . The effectiveness factors at different times for calcination with 0.3% SO 2 are shown in Figure , compared with those without SO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations